2020
DOI: 10.3390/su12218865
|View full text |Cite
|
Sign up to set email alerts
|

STEM Education in Secondary Schools: Teachers’ Perspective towards Sustainable Development

Abstract: Young people are the future of society and agents for social change, and so it is crucial to provide education that not only equips them with knowledge and skills but also changes their attitudes and behavior towards sustainable development. This study provides a review on how pedagogical approaches in science, technology, engineering, and mathematics (STEM) education can be deployed to teach concepts of sustainability. It also shows how secondary school teachers perceived STEM education and how they applied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 59 publications
5
64
0
8
Order By: Relevance
“…The more that STEM activity designers integrate the disciplines, the more likely they are to adopt different tasks and investigate different learning outcomes. Integrated STEM disciplinary activities are deemed promising and therefore have been promoted by the UN for "sustainable development education" [65]. The findings revealed that researchers in the last 10 years did not focus on integrating STEM-related concepts in other disciplines.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…The more that STEM activity designers integrate the disciplines, the more likely they are to adopt different tasks and investigate different learning outcomes. Integrated STEM disciplinary activities are deemed promising and therefore have been promoted by the UN for "sustainable development education" [65]. The findings revealed that researchers in the last 10 years did not focus on integrating STEM-related concepts in other disciplines.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…In the literature review conducted by Smith and Watson (2016), the integration of STEM education with sustainability education was discussed, and it was suggested that individuals would apply STEM knowledge and skills to solve sustainability and environmental problems based on economic or international competition. In their study, Nguyen, Nguyen and Tran (2020) interviewed 635 teachers working in STEM disciplines in middle schools and stated that the teachers wanted to use STEM education to address real-life sustainability problems such as pollution, sustainable consumption and production, energy and water saving. In the study conducted by Suh and Han (2019) on 42 university students, it was investigated how a STEM project affected student competencies related to sustainability by using a mathematical modelling applied for six weeks in mathematics lessons.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature review briefly summarized above, through the integration of sustainable development education with STEM, individuals are expected to use their STEM knowledge and skills to solve current sustainability problems or future economic, environmental and social problems in order to achieve a goal of sustainable life (Nguyen et al, 2020;Smith & Watson, 2016;Suh & Han, 2019). In addition, with STEM education, it is emphasized that individuals should acquire environmental information, develop a positive attitude towards the environment and develop environmentally friendly behaviours (Candan-Helvaci & Helvaci, 2019;Özçakır-Sümen & Çalışıcı, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, schools can be regarded as agents of change that can modify the lives of children and promote sustainable development, that is, sustainable use of water. Moreover, the kind of education secondary schools provide must not only equip them with skills and knowledge but also modify their attitude and behaviour leading towards water sustainability (Nguyen, Nguyen & Tran, 2020).…”
Section: Introductionmentioning
confidence: 99%